The effects of oblique waves and currents on the loadings and performance of tidal turbines. (15th September 2018) - Martinez, Rodrigo; Payne, Grégory S.; Bruce, Tom
Abstract: Tidal energy exploitation is at an early deployment stage and costs need to be reduced to improve the long term economic viability of the sector. High costs of tidal turbines are, in part, the result of load uncertainties, which lead to the use of high factors of safety in the design to ensure survival. One of the most important causes of uncertainty is hydrodynamic loadings. To date, most of the scaled model experiments with horizontal axis turbines investigating this issue have been carried out with collinear wave and current directions. To the authors' knowledge, the work presented herein is the first experimental investigation of a horizontal axis turbine model subjected to combined oblique waves and current. Turbine performance and loading are measured for a 1:15 scale model tested in the FloWave circular, combined wave and current basin at the University of Edinburgh (UK). Three different flow directions were tested and each of them were also combined with regular waves in three different directions non-collinear with the flow. Fifteen physical quantities were measured including flow velocity, rotor and foundation loads and turbine speed. Characterisation of loads and turbine performance in those oblique current and wave conditions are presented. Waves affect means and standard deviation of rotor power and thrust, but off-axis waves are associated with lower thrust loads than head-on waves. Compared to current only, rotor torque and thrust standard deviations are higher in the presence of waves and almost twice as high when the wave crest is parallel to the rotor plan. The experimental data associated with this article can be downloaded from http://dx.doi.org/10.7488/ds/2360 . Highlights: Novel basin testing with a 1.2m diameter turbine in wave-current interaction. Turbine performance in frequency and time domain at 0°, −10° and −20° (no waves). Turbine loads in frequency and time domain with non-collinear waves and currents. Torque, thrust and RPM measurements in turbine. New advice on influence of waves, in-line with, and oblique to flow.